2019
DOI: 10.3390/ijms20030625
|View full text |Cite
|
Sign up to set email alerts
|

Increased HLA-G Expression in Term Placenta of Women with a History of Recurrent Miscarriage Despite Their Genetic Predisposition to Decreased HLA-G Levels

Abstract: Human leukocyte antigen (HLA)-G is an immune modulating molecule that is present on fetal extravillous trophoblasts at the fetal-maternal interface. Single nucleotide polymorphisms (SNPs) in the 3 prime untranslated region (3′UTR) of the HLA-G gene can affect the level of HLA-G expression, which may be altered in women with recurrent miscarriages (RM). This case-control study included 23 women with a medical history of three or more consecutive miscarriages who delivered a child after uncomplicated pregnancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…In particular, in vitro studies on JEG-3 cells have suggested that over-expression of miR-133a may be responsible for decreased HLA-G expression, providing evidence that miR-133a regulates HLA-G expression by reducing translation and could be involved in the pathogenesis of unexplained RM [39]. Consistently, HLA-G was found to be increased in term placentas of women with a previous history of RM compared to women without previous adverse pregnancy outcomes [40]. On the other hand, in a recent meta-analysis, no differences in terms of uterine NK levels have been found between women with RM and normal pregnancy outcomes [41].…”
Section: Miscarriagementioning
confidence: 89%
“…In particular, in vitro studies on JEG-3 cells have suggested that over-expression of miR-133a may be responsible for decreased HLA-G expression, providing evidence that miR-133a regulates HLA-G expression by reducing translation and could be involved in the pathogenesis of unexplained RM [39]. Consistently, HLA-G was found to be increased in term placentas of women with a previous history of RM compared to women without previous adverse pregnancy outcomes [40]. On the other hand, in a recent meta-analysis, no differences in terms of uterine NK levels have been found between women with RM and normal pregnancy outcomes [41].…”
Section: Miscarriagementioning
confidence: 89%
“…Accordingly, HLA-G*01:01:02/01:01:02 genotype concordance between mother and her child was shown to increase the risk of oral infection of the child by any HPV genotype and/or HR-HPV genotypes (OR 2.45) [23]. This raised the possibility that oral HPV infections detected in young women might be determined by their mother's HLA-G status [25].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have assessed the associations between HLA-G polymorphism and female reproductive health [25,26]. HLA-G seems to play a major role as a suppressor of the immune response at the maternal-fetal interface as well as in placental angiogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule inhibits immune responses and induces the production of inhibitory and regulatory cells [9]. Changes in HLA-G ex-pression have been reported in the tissues of RPL patient [13]. Nucleotide changes in the promoter may affect HLA-G expression level by altering binding affinity that target transcription factors [16].…”
Section: Introductionmentioning
confidence: 99%